Thiolated Mesoporous Silica Nanoparticles as an Immunoadjuvant to Enhance Efficacy of Intravesical Chemotherapy for Bladder Cancer - Chen, Cheng‐Che; Fa, Yu‐Chen; Kuo, Yen‐Yu; Liu, Yi‐Chun; Lin, Chih‐Yu; Wang, Xin‐Hui; Lu, Yu‐Huan; Chiang, Yu‐Han; Yang, Chia‐Min; Wu, Li‐Chen; Ho, Ja‐an Annie (Advanced science, 2023)
The characteristics of global prevalence and high recurrence of bladder cancer has led numerous efforts to develop new treatments. The spontaneous voiding and degradation of the chemodrug hamper the efficacy and effectiveness of intravesical chemotherapy following tumor resection. Herein, the externally thiolated hollow mesoporous silica nanoparticles (MSN‐SH(E)) is fabricated to serve as a platform for improved bladder intravesical therapy. Enhanced mucoadhesive effect of the thiolated nanovector is confirmed with porcine bladder. The permeation‐enhancing effect is also verified, and a fragmented distribution pattern of a tight junction protein, claudin‐4, indicates the opening of tight junction. Moreover, MSN‐SH(E)‐associated reprogramming of M2 macrophages to M1‐like phenotype is observed in vitro. The antitumor activity of the mitomycin C (MMC)‐loaded nanovector (MMC@MSN‐SH(E)) is more effective than that of MMC alone in both in vitro and in vivo. In addition, IHC staining is used to analyze IFN‐γ, TGF‐β1, and TNF‐α. These observations substantiated the significance of MMC@MSN‐SH(E) in promoting anticancer activity, holding the great potential for being used in intravesical therapy for non‐muscle invasive bladder cancer (NMIBC) due to its mucoadhesivity, enhanced permeation, immunomodulation, and prolonged and very efficient drug exposure. The nanovectors, mitomycin C (MMC)‐loaded, externally thiolated hollow mesoporous silica nanoparticles (MSN‐SH(E)), are confirmed to be helpful in promoting anticancer activity, holding the great potential for being used in intravesical therapy for non‐muscle invasive bladder cancer due to its mucoadhesivity, enhanced permeation, immunomodulation and prolonged and very efficient drug exposure.